Architectural quality in competitions. A dialogue based assessment of design proposals - Rönn, Magnus (FormAkademisk, 2011)
This article is the outcome of a comprehensive study of architectural competitions in the Nordic countries (1999-2000). The vital content of the research is derived from a series of meticulously conducted interviews with key actors including 18 highly qualified and experienced experts from the jury members representing clients, architectural associations and competitors. The study refers to quality as a key-concept and a main source of conceiving, judging and selecting a prize winner. It is possible to articulate how architectural quality issues are met by jury members; how they are being communicated; and how a winner is nominated. The study provides insight into how the concept of quality in architectural design is understood in practice. Quality is identified through design criteria in a dialogue-based assessment of architecture and urban design projects. The assumption is that the judgment and evaluation of entries in competitions are strongly connected to the leading values, norms, regulations, organizations and traditions in Scandinavia. When quality is contextually bound, the assessment becomes a question of how the solutions fit the specific plot. These issues in a competition process cause uncertainties and discrepancies in judging and selection. However, while the main role of jury members is to agree upon the most appropriate solutions, they finally succeed in designating the best entry through their cumulated tacit knowledge and well-trained eyes. Competence and consensus are therefore two essential factors that make jury members feel confident in their final choice of a winner.